2007
DOI: 10.1029/2006ja011888
|View full text |Cite
|
Sign up to set email alerts
|

Observations of daytime F2‐layer stratification under the southern crest of the equatorial ionization anomaly region

Abstract: Ionospheric vertical sounding observations are being carried out at Sao Jose dos Campos (23.2°S, 45.9°W; dip latitude 17.6°S), Brazil, under the southern crest of the equatorial ionization anomaly (EIA) since August 2000. In this paper, we present and discuss the observations of daytime F2‐layer stratification near the crest of EIA, for the first time, under magnetically quiet high solar activity conditions. Three examples and a year of statistics are presented. The F2‐layer stratification and F3‐layer were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
3
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 29 publications
5
65
3
4
Order By: Relevance
“…Their model result shows that an upward E × B drift with ordinary neutral wind cannot produce the humps in the latitudinal variation of TEC as in the observation. The mechanism suggested by Thampi et al [54] resembles that of Fagundes et al [26] for the EIA region. However, they have not calculated the wave parameters through the ionosonde data to rule out possibility of the ordinary F3 layer which have the following signature: (a) it remains at the same virtual height and does not propagate downward to lower frequencies as a gravity wave would be expected to do; (b) no periodicity is observed in the intensity of the cusp.…”
Section: Mechanism Of the Quiet-time F3mentioning
confidence: 63%
See 3 more Smart Citations
“…Their model result shows that an upward E × B drift with ordinary neutral wind cannot produce the humps in the latitudinal variation of TEC as in the observation. The mechanism suggested by Thampi et al [54] resembles that of Fagundes et al [26] for the EIA region. However, they have not calculated the wave parameters through the ionosonde data to rule out possibility of the ordinary F3 layer which have the following signature: (a) it remains at the same virtual height and does not propagate downward to lower frequencies as a gravity wave would be expected to do; (b) no periodicity is observed in the intensity of the cusp.…”
Section: Mechanism Of the Quiet-time F3mentioning
confidence: 63%
“…Vasiliev [25] suggested that with increase of distance from equator, the role of internal gravity waves in the formation of the equatorial F2 layer stratifications increases. This hypothesis is used at present to explain the formation of the stratifications at the latitudes of the EIA crests in quiet geomagnetic conditions [26].…”
Section: Theoretical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations suggest that the distortion in the equatorial electron density profile, associated with a movement toward the base of the F 2 layer as magnetic field lines, descended with increasing latitude. Fagundes et al [2007] reported stratification of the F 2 layer over an equatorial anomaly crest location in Brazil, which was mainly considered as the result of the propagation of atmospheric gravity waves (AGWs) often observed in the middle latitudes [Heisler, 1962].…”
Section: Introductionmentioning
confidence: 99%